Logarithmic loop corrections, moduli stabilisation and de Sitter vacua in string theory - Ignatios Antoniadis; Yifan Chen; George K. Leontaris (Journal of High Energy Physics)
Abstract We study string loop corrections to the gravity kinetic terms in type IIB com- pactifications on Calabi-Yau threefolds or their orbifold limits, in the presence of D7-branes and orientifold planes. We show that they exhibit in general a logarithmic behaviour in the large volume limit transverse to the D7-branes, induced by a localised four-dimensional Einstein-Hilbert action that appears at a lower order in the closed string sector, found in the past. Here, we compute the coefficient of the logarithmic corrections and use them to provide an explicit realisation of a mechanism for Kähler moduli stabilisation that we have proposed recently, which does not rely on non-perturbative effects and lead to de Sit- ter vacua. Our result avoids no-go theorems of perturbative stabilisation due to runaway potentials, in a way similar to the Coleman-Weinberg mechanism, and provides a counter example to one of the swampland conjectures concerning de Sitter vacua in quantum grav- ity, once string loop effects are taken into account; it thus paves the way for embedding the Standard Model of particle physics and cosmology in string theory.